THE PREFERRED STYLES AND CHARACTERISTICS OF FASHION ATTIRE EMBRACED BY MALAYSIAN MUSLIMAH ICONS AND CELEBRITIES - Zaleha Arshad; Asliza Aris; Zainuddin Md Nor; Arasinah Kamis; Sri Endah Wahyuningsih; Kokom Kamariah; Adhi Kusumastuti; Farah Najwa Ahmad Fuad, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
This study investigates the fashion preferences and attire choices of prominent Malaysian Muslimah icons and celebrities. The study aims to understand the factors that shape their fashion decisions and the broader impact of these choices on societal fashion trends while examining the interplay between Islamic dress standards and contemporary fashion trends. Employing qualitative methods including in-depth interviews and document analysis, the research delves into the factors shaping their fashion decisions and the broader impact of these choices on societal trends. Key findings reveal a dynamic negotiation between religious adherence, cultural expression, and global fashion influences. The study identifies themes such as the significance of modesty, economic considerations, public perception, comfort priorities and the influence of international trends on Islamic attire. The research concludes that Malaysian Muslimah icons and celebrities navigate a nuanced balancing act, reconciling their religious and cultural identity with the ever-evolving global fashion landscape. Their choices reflect individual preferences and significantly influence societal fashion trends, positioning them as trendsetters in the Islamic fashion industry, bridging tradition and modernity. This study illuminates the complex context of fashion decisions for this group and paves the way for further exploration of the evolving landscape of Islamic fashion in Malaysia.